Well cementation cement slurry and preparation method and application thereof
By mixing active materials and hollow glass microspheres into oil well cementing cementing cement slurry with high activity, low density corrosion resistance, the problem of cement ring seal integrity of high sulfur-containing natural gas wells and CCUS wells is solved, and high quality is achieved Rapid well construction and long-term sealing effect.
Patent Information
- Application Number
- CN202311005680.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-08-10
AI Technical Summary
High sulfur-containing natural gas wells and CCUS wells have challenges in wellbore seal integrity. Conventional density cement slurry can easily lead to well leakage. Ordinary floating beads have poor settlement stability, making it difficult to ensure the long-term seal integrity of cement rings.
A high-active, low-density, corrosion-resistant cementing cementing slurry is used to mix active materials, hollow glass microspheres, corrosion-resistant materials, tough materials and other key materials in oil well cement to form a tight stacking structure to improve the settlement stability of cement slurry and compressive strength.
It has achieved high-quality rapid well construction, ensured the long-term seal integrity of the cement ring, reduced the impact of stress and strain, and provided strong technical support for the exploration and development of high-sulfur natural gas wells and CCUS wells.
Smart Images

Figure CN119461954A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of well cementing, and relates to a well cementing cement slurry, and in particular to a well cementing cement slurry and a preparation method and application thereof. Background Art
[0003] High-sulfur natural gas wells and CCUS wells have high requirements for the long-term sealing integrity of the wellbore, and the cement ring sealing integrity is the core of the wellbore integrity. The cement ring sealing integrity is generally macroscopically manifested by the cementing quality and the wellhead annulus pressure, and is the key embodiment of cementing technology to ensure good interlayer isolation. However, high-sulfur natural gas wells and domestic CCUS wells in the Sichuan Basin of my country often have the problem of low formation pressure bearing capacity, and hydrogen sulfide and carbon dioxide have high requirements for the long-term corrosion resistance of the cement ring. This puts high demands on the performance of cementing cement slurry in order to solve various cementing problems that arise during exploration, development and production.
[0004] After preliminary research, the inventors found that: (1) If conventional density cement slurry is used for cementing, leakage is likely to occur during the construction process, and it is difficult for cement slurry to return to the ground. Although the annulus can be remedied by back-injecting cement slurry, the cement ring cannot ensure continuity, and empty casing is likely to appear in the annulus. In subsequent operations or later production processes, the cement ring and casing will be affected by various periodic stresses and strains. Therefore, the empty casing without cement ring sealing is prone to deformation. After a long time, the casing is prone to damage, forming an interlayer crossflow channel, affecting the safety and long-term production of the wellbore. (2) If ordinary floating bead low-density cement slurry is used for cementing, the cement slurry has poor sedimentation stability. Under high pressure at the bottom of the well, the increased density of the cement slurry is prone to leakage, and the cement slurry is difficult to return to the ground. The compressive strength of the cement stone and the cement ring interface bonding quality are difficult to guarantee, which is not conducive to leakage prevention and long-term resistance to hydrogen sulfide and carbon dioxide corrosion.
[0005] It can be seen that how to provide a high-activity, low-density, corrosion-resistant cementing slurry and its preparation method to achieve high-quality and rapid well construction, ensure the long-term sealing integrity of the cement ring, and provide strong technical support for the large-scale exploration and development of high-sulfur natural gas wells and CCUS wells and reduce the risks of wellhead gas blowby and annulus pressure has become an urgent problem that technical personnel in this field need to solve. Summary of the invention
[0006] The purpose of the present invention is to provide a cementing slurry and a preparation method and application thereof, wherein the cementing slurry realizes high-quality and rapid well construction, ensures the long-term sealing integrity of the cement ring, and provides strong technical support for the large-scale exploration and development of high-sulfur natural gas wells and CCUS wells and the reduction of the risks of wellhead gas blowby and annulus pressure.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a cementing slurry, which comprises oil well cement, active material, hollow glass microspheres, corrosion-resistant material, toughness material, suspending agent, dispersant, fluid loss reducer, retarder, defoaming agent and water.
[0009] The density of the cementing slurry is 1.2-1.6 g / cm 3 , for example, it can be 1.2 g / cm 3 , 1.25g / cm 3 , 1.3g / cm 3 , 1.35g / cm 3 , 1.4g / cm 3 , 1.45g / cm 3 , 1.5g / cm 3 , 1.55g / cm 3 or 1.6 g / cm 3 , but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0010] The present invention is based on the close packing theory, and mixes active materials, hollow glass microspheres and other key materials in oil well cement to obtain a high-activity, low-density, corrosion-resistant cementing slurry with good sedimentation stability, fast strength-building time, high compressive strength, low elastic modulus, and strong corrosion resistance. It can reduce the influence of stress and strain in the production process of high-sulfur natural gas wells and CCUS wells, realize high-quality and rapid well construction, and ensure the long-term sealing integrity of the cement ring. It provides strong technical support for the large-scale exploration and development of high-sulfur natural gas wells and CCUS wells and the reduction of the risks of wellhead gas blowby and annulus pressure.
[0011] Preferably, the cementing slurry comprises, by weight:
[0012]
[0013] In the present invention, the weight proportion of the active material is 13-38 parts, for example, it can be 13 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, 30 parts, 32 parts, 34 parts, 36 parts or 38 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0014] In the present invention, the weight proportion of the hollow glass microspheres is 10-75 parts, for example, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts or 75 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0015] In the present invention, the weight proportion of the corrosion-resistant material is 6-16 parts, for example, it can be 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts or 16 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0016] In the present invention, the weight proportion of the tough material is 1-9 parts, for example, it can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts or 9 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] In the present invention, the weight proportion of the suspending agent is 1-2 parts, for example, it can be 1 part, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts or 2 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] In the present invention, the weight proportion of the dispersant is 1-2 parts, for example, it can be 1 part, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts or 2 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] In the present invention, the weight proportion of the fluid loss additive is 4-6 parts, for example, 4 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts, 5 parts, 5.2 parts, 5.4 parts, 5.6 parts, 5.8 parts or 6 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] In the present invention, the weight proportion of the retarder is 1-2 parts, for example, it can be 1 part, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts or 2 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] In the present invention, the weight proportion of the defoaming agent is 0.1-0.5 parts, for example, it can be 0.1 parts, 0.15 parts, 0.2 parts, 0.25 parts, 0.3 parts, 0.35 parts, 0.4 parts, 0.45 parts or 0.5 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] In the present invention, the weight proportion of water is 80-120 parts, for example, it can be 80 parts, 85 parts, 90 parts, 95 parts, 100 parts, 105 parts, 110 parts, 115 parts or 120 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] Preferably, in parts by weight, the active material comprises:
[0024]
[0025] In the present invention, the model of the reinforcing material may be DRB-1S, the model of the expansion toughening material may be DRE-3S, and the model of the early strength agent may be DRA-1S, as long as the corresponding functions can be achieved, so the specific composition of each material is not particularly limited here.
[0026] In the present invention, the weight proportion of the ultrafine silicon is 2-5 parts, for example, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] In the present invention, the weight proportion of the reinforcing material is 10-20 parts, for example, it can be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] In the present invention, the weight proportion of the expansion toughening material is 1-10 parts, for example, it can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] In the present invention, the weight proportion of the early strength agent is 0-3 parts, for example, it can be 0 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts or 3 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] Preferably, the average particle size of the ultrafine silicon is 0.1-0.3 μm, for example, it can be 0.1 μm, 0.12 μm, 0.14 μm, 0.16 μm, 0.18 μm, 0.2 μm, 0.22 μm, 0.24 μm, 0.26 μm, 0.28 μm or 0.3 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] Preferably, the corrosion-resistant material comprises, by weight:
[0032] 6-10 parts of elastic material;
[0033] 0-6 copies of anti-channeling material.
[0034] In the present invention, the model of the elastic material may be DRT-2S, and the model of the anti-channeling material may be DRT-1S, as long as the corresponding functions can be achieved, so the specific composition of each material is not particularly limited here.
[0035] In the present invention, the weight proportion of the elastic material is 6-10 parts, for example, it can be 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts or 10 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] In the present invention, the weight proportion of the anti-channeling material is 0-6 parts, for example, it can be 0 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts or 6 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] Preferably, in parts by weight, the tough material comprises:
[0038] 1-6 parts of toughening material;
[0039] 0-3 parts of fiber material.
[0040] In the present invention, the model of the toughening material may be DRE-1S, and the model of the fiber material may be DRE-5S, as long as the corresponding functions can be achieved, so the specific composition of each material is not particularly limited herein.
[0041] In the present invention, the weight proportion of the toughening material is 1-6 parts, for example, it can be 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts or 6 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] Preferably, the suspending agent comprises a graft copolymer suspending agent, and the model may be DRK-3S.
[0043] Preferably, the dispersant includes a ketone-aldehyde oil well cement dispersant, and the model may be DRS-1S.
[0044] Preferably, the fluid loss additive comprises a polyacrylamide solid fluid loss additive, and the model may be DRF-1S.
[0045] Preferably, the retarder comprises an organic acid retarder, and the model may be DRH-1L.
[0046] Preferably, the defoaming agent includes polydimethylsiloxane, and the model may be DRX-1L.
[0047] In a second aspect, the present invention provides a method for preparing the cementing slurry as described in the first aspect, the preparation method comprising the following steps:
[0048] (1) mixing oil well cement, active material, hollow glass microspheres, corrosion resistant material, toughening material, suspending agent, dispersing agent and fluid loss additive, and stirring evenly to obtain a dry mix;
[0049] (2) mixing a retarder, a defoamer and water, and stirring evenly to obtain a wet mixed solution;
[0050] (3) Mixing the dry mixture obtained in step (1) and the wet mixture obtained in step (2), and continuing to stir after the dry mixture is completely wetted to obtain cement slurry.
[0051] There is no particular order in which steps (1) and (2) are performed.
[0052] Preferably, the mixing method in step (3) includes: pouring the dry mix evenly into the wet mix solution, and stirring during the pouring process.
[0053] Preferably, the stirring speed is 3800-4200 rpm, for example, 3800 rpm, 3900 rpm, 4000 rpm, 4100 rpm or 4200 rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] Preferably, in step (3), stirring is continued for 30-40 seconds after the dry mixture is completely wetted, for example, it can be 30 seconds, 31 seconds, 32 seconds, 33 seconds, 34 seconds, 35 seconds, 36 seconds, 37 seconds, 38 seconds, 39 seconds or 40 seconds, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0055] As a preferred technical solution of the second aspect of the present invention, the preparation method comprises the following steps:
[0056] (1) mixing oil well cement, active material, hollow glass microspheres, corrosion resistant material, toughening material, suspending agent, dispersing agent and fluid loss additive according to weight proportions, and stirring evenly to obtain a dry mix;
[0057] (2) mixing a retarder, a defoamer and water according to weight proportions, and stirring evenly to obtain a wet mixed solution;
[0058] (3) Pour the dry mix obtained in step (1) evenly into the wet mix obtained in step (2), stirring at 3800-4200 rpm during the pouring process, and continue stirring for 30-40 seconds after the dry mix is completely wetted to obtain cement slurry.
[0059] There is no particular order in which steps (1) and (2) are performed.
[0060] In a third aspect, the present invention provides a use of the cementing slurry as described in the first aspect, wherein the cementing slurry is used for sealing the cement ring during the production process of sour natural gas wells and / or CCUS wells.
[0061] Compared with the prior art, the present invention has the following beneficial effects:
[0062] The present invention is based on the close packing theory, and mixes active materials, hollow glass microspheres and other key materials in oil well cement to obtain a high-activity, low-density, corrosion-resistant cementing slurry with good sedimentation stability, fast strength-building time, high compressive strength, low elastic modulus, and strong corrosion resistance. It can reduce the influence of stress and strain in the production process of high-sulfur natural gas wells and CCUS wells, realize high-quality and rapid well construction, and ensure the long-term sealing integrity of the cement ring. It provides strong technical support for the large-scale exploration and development of high-sulfur natural gas wells and CCUS wells and the reduction of the risks of wellhead gas blowby and annulus pressure. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 The relationship curves of the triaxial compressive strength, the compressive strength loss rate after corrosion and the cement slurry density of the cementing slurry obtained in Examples 1-5 are shown;
[0064] Figure 2 The relationship curve between the triaxial compressive strength and permeability of the cementing slurry obtained in Comparative Examples 1-4 and the amount of active material added;
[0065] Figure 3 The relationship curve between the compressive strength loss rate after corrosion and the amount of corrosion-resistant material added of the cementing slurry obtained in Comparative Examples 5-8;
[0066] Figure 4 The curves are the relationship between the triaxial Young's modulus and the amount of toughness material added of the cementing slurry obtained in Comparative Examples 9-11. DETAILED DESCRIPTION
[0067] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0068] Example 1
[0069] The present embodiment provides a cementing slurry and a preparation method thereof. The material composition and proportion of the cementing slurry are shown in Table 1 below, in parts by weight.
[0070] Table 1
[0071]
[0072]
[0073] In the above table, high sulfate resistance (HSR) G-grade oil well cement is produced by Jiahua Special Cement Co., Ltd.; ultrafine silica is produced by Shanggao County Polysilicon Mining Co., Ltd.; T60 hollow glass microspheres are produced by China Steel Group Ma'anshan Mining Research Institute Co., Ltd.; reinforcing material DRB-1S, expansion toughening material DRE-3S, early strength agent DRA-1S, elastic material DRT-2S, anti-channeling material DRT-1S, toughening material DRE-1S, fiber material DRE-5S, graft copolymer suspending agent DRK-3S, ketone aldehyde oil well cement dispersant DRS-1S, polyacrylamide solid fluid loss reducer DRF-1S, organic acid retarder DRH-1L and polydimethylsiloxane DRX-1L are all produced by China Petroleum Engineering Technology Research Institute Co., Ltd.
[0074] After testing, the density of the cement slurry obtained in this example is 1.20 g / cm 3 .
[0075] In this embodiment, the method for preparing the cementing slurry comprises the following steps:
[0076] (1) mixing oil well cement, active material, hollow glass microspheres, corrosion resistant material, toughening material, suspending agent, dispersing agent and fluid loss additive according to weight proportions, and stirring evenly to obtain a dry mix;
[0077] (2) mixing a retarder, a defoamer and water according to weight proportions, and stirring evenly to obtain a wet mixed solution;
[0078] (3) Pour the dry mix obtained in step (1) evenly into the wet mix obtained in step (2), stirring at 4000±200 rpm during the pouring process, and continue stirring for 35 seconds after the dry mix is completely wetted to obtain cement slurry.
[0079] Example 2-3
[0080] Examples 2-3 respectively provide a cementing slurry and a preparation method thereof. The material composition and proportion of the cementing slurry are shown in Table 2 below, calculated by weight.
[0081] Table 2
[0082]
[0083] In the above table, the manufacturers of various material components are the same as those in Example 1, so they are not described here.
[0084] After testing, the density of the cement slurry obtained in Example 2 was 1.30 g / cm 3 The density of the cement slurry obtained in Example 3 is 1.40 g / cm 3 .
[0085] The preparation method of the cementing slurry described in Example 2-3 is the same as that in Example 1, so it will not be described here in detail.
[0086] Embodiment 4-5
[0087] Examples 4-5 respectively provide a cementing slurry and a preparation method thereof. The material composition and proportion of the cementing slurry are shown in Table 3 below, in parts by weight.
[0088] Table 3
[0089]
[0090]
[0091] In the above table, the manufacturers of various material components are the same as those in Example 1, so they are not described here.
[0092] After testing, the density of the cementing slurry obtained in Example 4 was 1.50 g / cm 3 The density of the cement slurry obtained in Example 5 is 1.60 g / cm 3 .
[0093] The preparation method of the cementing slurry described in Examples 4-5 is the same as that in Example 1, so it will not be described here in detail.
[0094] Comparative Example 1
[0095] This comparative example provides a cementing slurry and a preparation method thereof. The material composition and proportion of the cementing slurry are shown in Table 4 below, calculated by weight.
[0096] Table 4
[0097]
[0098]
[0099] In the above table, the manufacturers of various material components are the same as those in Example 1, so they are not described here.
[0100] After testing, the density of the cement slurry obtained in this comparative example is 1.30 g / cm 3 .
[0101] The preparation method of the cementing slurry described in this comparative example is the same as that in Example 1, so it will not be described here in detail.
[0102] Comparative Examples 2-3
[0103] Comparative Examples 2-3 respectively provide a cementing slurry and a preparation method thereof. The material composition and proportion of the cementing slurry are shown in Table 5 below, calculated by weight.
[0104] Table 5
[0105]
[0106]
[0107] In the above table, the manufacturers of various material components are the same as those in Example 1, so they are not described here.
[0108] After testing, the density of the cement slurry obtained in Comparative Example 2 was 1.30 g / cm 3 The density of the cement slurry obtained in Comparative Example 3 is 1.30 g / cm 3 .
[0109] The preparation method of the cementing slurry described in Comparative Example 2-3 is the same as that in Example 1, so it will not be described here in detail.
[0110] Comparative Examples 4-5
[0111] Comparative Examples 4-5 respectively provide a cementing slurry and a preparation method thereof. The material composition and proportion of the cementing slurry are shown in Table 6 below, calculated by weight.
[0112] Table 6
[0113]
[0114]
[0115] In the above table, the manufacturers of various material components are the same as those in Example 1, so they are not described here.
[0116] After testing, the density of the cement slurry obtained in Comparative Example 4 was 1.30 g / cm 3 The density of the cement slurry obtained in Comparative Example 5 is 1.30 g / cm 3 .
[0117] The preparation method of the cementing slurry described in Comparative Example 4-5 is the same as that in Example 1, so it will not be described here in detail.
[0118] Comparative Examples 6-7
[0119] Comparative Examples 6-7 respectively provide a cementing slurry and a preparation method thereof. The material composition and proportion of the cementing slurry are shown in Table 7 below, calculated by weight.
[0120] Table 7
[0121]
[0122]
[0123] In the above table, the manufacturers of various material components are the same as those in Example 1, so they are not described here.
[0124] After testing, the density of the cement slurry obtained in Comparative Example 6 was 1.30 g / cm 3 The density of the cement slurry obtained in Comparative Example 7 is 1.30 g / cm 3 .
[0125] The preparation method of the cementing slurry described in Comparative Examples 6-7 is the same as that in Example 1, so it will not be described here in detail.
[0126] Comparative Examples 8-9
[0127] Comparative Examples 8-9 respectively provide a cementing slurry and a preparation method thereof. The material composition and proportion of the cementing slurry are shown in Table 8 below, calculated by weight.
[0128] Table 8
[0129]
[0130]
[0131] In the above table, the manufacturers of various material components are the same as those in Example 1, so they are not described here.
[0132] After testing, the density of the cement slurry obtained in Comparative Example 8 was 1.30 g / cm 3 The density of the cement slurry obtained in Comparative Example 9 is 1.30 g / cm 3 .
[0133] The preparation method of the cementing slurry described in Comparative Examples 8-9 is the same as that in Example 1, so it will not be described here in detail.
[0134] Comparative Examples 10-11
[0135] Comparative Examples 10-11 respectively provide a cementing slurry and a preparation method thereof. The material composition and proportion of the cementing slurry are shown in Table 9 below, calculated by weight.
[0136] Table 9
[0137]
[0138] In the above table, the manufacturers of various material components are the same as those in Example 1, so they are not described here.
[0139] After testing, the density of the cement slurry obtained in Comparative Example 10 was 1.30 g / cm 3 The density of the cement slurry obtained in Comparative Example 11 is 1.30 g / cm 3 .
[0140] The preparation method of the cementing slurry described in Comparative Examples 10-11 is the same as that in Example 1, so it will not be described here in detail.
[0141] Performance Test:
[0142] The cementing slurries obtained in Examples 1-5 and Comparative Examples 1-11 were subjected to comprehensive performance tests. Specifically, sample preparation and sedimentation stability, API water loss, thickening time, triaxial compressive strength, Young's modulus, permeability, and compressive strength loss rate after corrosion were determined in accordance with national standards such as GB / T 19139-2012 "Test methods for oil well cement" and SYT 6466-2016 "Test methods for properties of oil well cement stone". The relevant test results are shown in Table 10 below.
[0143] Table 10
[0144]
[0145]
[0146] In the above table, the relevant test conditions are as follows:
[0147] (1) API dehydration test conditions: 65°C × 30 min;
[0148] (2) Triaxial compressive strength, triaxial Young's modulus, and permeability test conditions: 65°C × 20.7 MPa;
[0149] (3) Thickening time experimental conditions: 65°C × 35MPa × 30min;
[0150] (4) Experimental conditions for compressive strength loss rate after corrosion: total pressure 10 MPa, H2S partial pressure 1.5 MPa, CO2 partial pressure 1 MPa, corrosion at 65 °C for 7 days.
[0151] Figure 1 The graphs are the relationship between the triaxial compressive strength, the compressive strength loss rate after corrosion and the cement slurry density of the cementing slurries obtained in Examples 1-5.
[0152] Combination Figure 1As shown in Table 10, when the amount of active material, corrosion-resistant material and toughness material is the same, with the increase of cement paste density, the triaxial compressive strength of low-density cement paste shows an increasing trend, and the compressive strength loss rate after corrosion shows a decreasing trend, but overall 1.20-1.60 g / cm 3 The comprehensive performance of the low-density, high-activity, and corrosion-resistant cement slurry system can meet the technical requirements of high-sulfur gas wells and CCUS wells.
[0153] Figure 2 The relationship curves of the triaxial compressive strength and permeability of the cementing slurries obtained in Comparative Examples 1-4 and the amount of active materials added are shown.
[0154] Combination Figure 2 As shown in Table 10, with the increase of the amount of active material added, the triaxial compressive strength of the low-density cement paste shows an increasing trend, and the permeability shows a decreasing trend. This is because the incorporation of active materials causes the cement slurry system to undergo a crystal phase transition under certain temperature conditions. When the cement solidifies and hardens, the cement paste expands in volume, which compensates for shrinkage and tensions the steel bars to produce prestress, as well as fully fills the cement gap. Therefore, the compressive strength of the cement paste is improved, the permeability is significantly reduced, the cement ring can avoid volume shrinkage, and the structural integrity and mechanical integrity of the cement ring can be guaranteed under the action of alternating stress, which is beneficial to the stability of the casing-cement ring-formation coupling body, improves the isolation quality, and ensures the sealing integrity of the wellbore.
[0155] Figure 3 The graph is a relationship curve between the compressive strength loss rate after corrosion and the amount of corrosion-resistant material added of the cement slurry obtained in Comparative Examples 5-8.
[0156] Combination Figure 3 It can be seen from Table 10 that with the increase of the amount of corrosion-resistant materials added, the compressive strength loss rate of low-density cement paste after corrosion shows a decreasing trend. This is because with the addition of corrosion-resistant materials in cement paste, the corrosion rate of cement paste is reduced, which makes the compressive strength loss rate of cement paste after corrosion significantly reduced.
[0157] Figure 4 The curves are the relationship between the triaxial Young's modulus and the amount of toughness material added of the cementing slurry obtained in Comparative Examples 9-11.
[0158] Combination Figure 4 As shown in Table 10, due to the presence of certain pores inside conventional cement paste, the addition of tough materials fills the pores, forming bridges and inhibiting the development of gaps. With the increase in the amount of tough material added, the triaxial Young's modulus of low-density cement paste shows a decreasing trend. This is because when external forces act on cement paste, the tough material uses its own low elastic modulus characteristics to reduce the transmission coefficient of external forces, weaken the destructive force of external forces on the cement paste matrix, and achieve the purpose of protecting the mechanical integrity of cement paste.
[0159] Based on the above research results, it can be seen that the addition of active materials, corrosion-resistant materials and tough materials into low-density cement has little effect on the sedimentation stability, thickening time, API water loss and other properties of low-density cement. The triaxial compressive strength, permeability, triaxial Young's modulus, compressive strength loss rate after corrosion and other properties of cement paste are significantly improved, which is beneficial to improving the sealing integrity of cement ring wellbore in high-sulfur gas wells and CCUS wells, and can prevent annular gas blowby and wellhead pressure.
[0160] It can be seen that the present invention is based on the close packing theory, and mixes active materials, hollow glass microspheres and other key materials in oil well cement to obtain a high-activity, low-density, corrosion-resistant cementing slurry with good sedimentation stability, fast strength-building time, high compressive strength, low elastic modulus, and strong corrosion resistance. It can reduce the influence of stress and strain in the production process of high-sulfur natural gas wells and CCUS wells, realize high-quality and rapid well construction, and ensure the long-term sealing integrity of the cement ring, providing strong technical support for the large-scale exploration and development of high-sulfur natural gas wells and CCUS wells and reducing the risks of wellhead gas blowby and annulus pressure.
[0161] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A cementing slurry, characterized in that: The cementing slurry comprises oil well cement, active material, hollow glass microspheres, corrosion resistant material, toughness material, suspending agent, dispersant, fluid loss reducer, retarder, defoamer and water; The density of the cementing slurry is 1.2-1.6 g / cm 3 .
2. The cementing slurry according to claim 1, characterized in that: The cementing slurry comprises, by weight:
3. The cementing slurry according to claim 1 or 2, characterized in that: In terms of weight, the active material includes: Preferably, the average particle size of the ultrafine silicon is 0.1-0.3 μm.
4. The cementing slurry according to any one of claims 1 to 3, characterized in that: The corrosion-resistant material includes, by weight: 6-10 parts of elastic material; 0-6 copies of anti-channeling material.
5. The cementing slurry according to any one of claims 1 to 4, characterized in that: In terms of weight, the tough material includes: 1-6 parts of toughening material; 0-3 parts of fiber material.
6. The cementing slurry according to any one of claims 1 to 5, characterized in that: The suspending agent includes a graft copolymer type suspending agent; Preferably, the dispersant comprises a ketone-aldehyde oil well cement dispersant; Preferably, the fluid loss agent comprises a polyacrylamide solid fluid loss agent; Preferably, the retarder comprises an organic acid retarder; Preferably, the defoaming agent comprises polydimethylsiloxane.
7. A method for preparing cementing slurry according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) mixing oil well cement, active material, hollow glass microspheres, corrosion resistant material, toughening material, suspending agent, dispersing agent and fluid loss additive, and stirring evenly to obtain a dry mix; (2) mixing a retarder, a defoamer and water, and stirring evenly to obtain a wet mixed solution; (3) mixing the dry mixture obtained in step (1) and the wet mixture obtained in step (2), and continuing to stir after the dry mixture is completely wetted to obtain cement slurry; There is no particular order in which steps (1) and (2) are performed.
8. The preparation method according to claim 7, characterized in that: The mixing method in step (3) includes: pouring the dry mixed material evenly into the wet mixed solution, and stirring during the pouring process; Preferably, the stirring speed is 3800-4200 rpm; Preferably, in step (3), stirring is continued for 30-40 seconds after the dry mix is completely wetted.
9. The preparation method according to claim 7 or 8, characterized in that: The preparation method comprises the following steps: (1) mixing oil well cement, active material, hollow glass microspheres, corrosion resistant material, toughening material, suspending agent, dispersing agent and fluid loss additive according to weight proportions, and stirring evenly to obtain a dry mix; (2) mixing a retarder, a defoamer and water according to weight proportions, and stirring evenly to obtain a wet mixed solution; (3) pouring the dry mixture obtained in step (1) evenly into the wet mixture obtained in step (2), stirring at 3800-4200 rpm during the pouring process, and continuing to stir for 30-40 seconds after the dry mixture is completely wetted to obtain cement slurry; There is no particular order in which steps (1) and (2) are performed.
10. An application of the cementing slurry according to any one of claims 1 to 6, characterized in that: The cementing slurry is used for sealing the cement ring during the production process of sour natural gas wells and / or CCUS wells.
Citation Information
Patent Citations
Expanded flexible well cementing grout and preparation method thereof
CN104371678A
Low-density micro-expansion early-strength channeling-preventive oil well cement slurry and preparation method thereof
CN105062441A
Low-temperature high-strength tough cement paste and preparation method and application thereof
CN106986584A
Low-density anti-leakage cement composition, low-density anti-leakage cement paste and preparation method of low-density anti-leakage cement paste
CN109095822A